BEYOND CONSOLIDATING POWER: THE LOGIC AND ADAPTABILITY OF POLITICAL PURGES IN STALIN’S SOVIET UNION, SADDAM’S IRAQ, AND THE ASSAD’S SYRIA - Tarkhani, Soran (Humanities Journal of University of Zakho, 2025)
This study analyzes the role of purges as systemic mechanisms of governance within Stalin’s Soviet Union, Saddam Hussein’s Iraq, and Assad’s Syria. While commonly perceived as instruments for power consolidation, this paper argues that purges extend beyond tactical purposes to function as institutionalized practices. These mechanisms enforced elite loyalty, restructured power dynamics, and suppressed dissent, serving as adaptive strategies for authoritarian resilience. The analysis identifies shared patterns, such as a dual-phase structure targeting external threats before focusing on internal rivals, while also exploring ideological, structural, and personalist dimensions. Despite ideological differences—Marxist-Leninist revolution in Stalin’s USSR, Ba’athist Arab nationalism in Iraq, and sectarian authoritarianism in Syria—the study reveals a universal adaptability of purges to the vulnerabilities of authoritarian regimes. Using Wintrobe’s (1998) concept of the “fear equilibrium” and Tilly’s (2003) theory of institutionalized violence, this comparative framework advances the understanding of authoritarian resilience and the strategic role of violence in state control. .